PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DALAM MATERI PERANGKAT KERAS KOMPUTER TERHADAP PEMAHAMAN KONSEP SISWA KELAS VII DI SMPN 15 PONTIANAK - Fajar Firdiansyah; Yudi Darma; Chandra Lesmana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low conceptual understanding of students in computer hardware material due to the limited use of interactive learning media. Students often face difficulties in visualizing computer components such as CPU, RAM, and motherboard. Therefore, this research aims to develop and determine the feasibility of Augmented Reality (AR)-based learning media to improve students' conceptual understanding. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study included material experts, media experts, teachers, and students of class VII at SMPN 15 Pontianak. Data collection techniques used questionnaires, interviews, and documentation, while data analysis was conducted using descriptive quantitative methods. The results showed that the AR-based learning media developed was categorized as very feasible. This is evidenced by the validation results from material and media experts, which fall into the very valid category, as well as positive responses from teachers and students indicating that the media is very practical. In addition, the effectiveness test results showed an improvement in students' conceptual understanding after using the media. Thus, AR-based learning media is appropriate to be used as an innovative and interactive alternative learning media to enhance students' understanding of computer hardware concepts.